2021
DOI: 10.1093/plphys/kiab279
|View full text |Cite
|
Sign up to set email alerts
|

Life history, diversity, and distribution in parasitic flowering plants

Abstract: A review of parasitic plant diversity and outstanding disjunct distributions according to an updated functional classification based on these plants’ life cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 146 publications
1
31
0
Order By: Relevance
“…It has been found that the fruits of C. filiformis floated for months in the Pacific ( Muir, 1933 ). These lead to an additional water-mediated dispersal hypothesis for this species ( Teixeira-Costa and Davis, 2021 ), but further evidence is lacking.…”
Section: Parasitic Habits and Host Range Of Cassythamentioning
confidence: 99%
See 3 more Smart Citations
“…It has been found that the fruits of C. filiformis floated for months in the Pacific ( Muir, 1933 ). These lead to an additional water-mediated dispersal hypothesis for this species ( Teixeira-Costa and Davis, 2021 ), but further evidence is lacking.…”
Section: Parasitic Habits and Host Range Of Cassythamentioning
confidence: 99%
“…Parasitic flowering plants either attach to host roots or shoots. They can be chlorophyllous and thus, capable of photosynthesis (hemiparasites) or not (holoparasites) and they can be further divided into four types: root vs. stem hemiparasites, and root vs. stem holoparasites ( Musselman and Press, 1995 ; Teixeira-Costa and Davis, 2021 ). They can also be classified as obligate parasites (which indicates that they need a host plant to acquire nutrients to survive after germination) and facultative parasites (which are capable of reaching maturity without attachment to the host) ( Shen et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 1.8% of the more than 300,000 known flowering plant species are parasitic, with haustorial parasites (c. 4,800 species) having evolved at least 12 times independently across the angiosperms and showing extremely diverse morphologies, ranging from large trees to tiny herbaceous plants ( Barkman et al, 2007 ; Westwood et al, 2010 ; Twyford, 2018 ; Nickrent, 2020 ). Depending on the site of attachment to the host, parasitic plants are classified into stem (aerial) or root parasites and based on whether these have retained or lost photosynthetic activities as hemiparasites or holoparasites, respectively ( Nickrent and Musselman, 2004 ; Têšitel, 2016 ; Yoshida et al, 2016 ; Teixeira-Costa and Davis, 2021 ). Hemiparasites are photosynthetically active but derive water, minerals, nutrients, and significant amounts of carbon from their hosts, whereas holoparasites lack photosynthetic activity and rely entirely on a host for carbon ( Poulin et al, 2011 ; Twyford, 2018 ; Nickrent, 2020 ; definitions of hemiparasites and other functional classifications reviewed in Têšitel, 2016 ; Teixeira-Costa and Davis, 2021 ).…”
Section: Introductionmentioning
confidence: 99%